Higher order involutes of a curve in quaternionic spaces - Yilmaz, Munevver Yildirim; Erdem, Esra (Palestine Polytechnic University, 2022)
[Abstract Not Available]
Keywords: Frenet curve; Frenet frame; Involute curve; Quaternionic curve; Quaternionic frame